Identification of an Intestinal Microbiota Signature Associated With the Severity of Necrotic Enteritis - Yang, Qing; Liu, Jing; Wang, Xiaofan; Robinson, Kelsy; Whitmore, Melanie A.; Stewart, Sydney N.; Zhao, Jiangchao; Zhang, Guolong (Frontiers in Microbiology, 2021)
Necrotic enteritis (NE), an economically devastating disease of poultry caused by pathogenic Clostridium perfringens, is known to induce small intestinal lesions and dysbiosis. However, the microbiota that is associated with NE severity is yet to be characterized. Here, we investigated the link between the ileal microbiota and disease severity in a chicken model of clinical NE using 16S rRNA gene sequencing. Our results indicated that richness and Shannon Index of the ileal microbiota were drastically reduced (P < 0.01) as NE was exacerbated. While the relative abundance of C. perfringens increased from 0.02% in healthy chickens to 58-70% in chickens with severe infection, a majority of the ileal microbes were markedly diminished, albeit varying in their sensitivity to NE. Compositionally, a large group of ileal microbes showed a significant correlation with NE severity. Firmicutes such as group A and B Lactobacillus, Lactobacillus reuteri, Subdoligranulum variabile, Mediterraneibacter, and Staphylococcus as well as two genera of Actinobacteria (Corynebacterium and Kocuria) and two highly related Cyanobacteria were progressively declined as NE was aggravated. Other Firmicutes such as Weissella, Romboutsia, Kurthia, Cuneatibacter, Blautia, and Aerococcus appeared much more sensitive and were rapidly abolished in chickens even with mild NE. On the other hand, Enterococcus cecorum and two Escherichia/Shigella species were only enriched in the ileal microbiota of chickens with extremely severe NE, while several other species such as Streptococcus gallolyticus and Bacteroides fragilis remained unaltered by NE. Functionally, secondary bile acid biosynthesis was predicted to be suppressed by NE, while biosynthesis of aromatic and branched-amino acids and metabolism of a majority of amino acids were predicted to be enhanced in the ileum of NE-afflicted chickens. These intestinal microbes showing a strong correlation with NE severity may provide important leads for the development of novel diagnostic or therapeutic approaches to NE and possibly other enteric diseases.